QSAR : rational approaches to the design of bioactive compounds : proceedings of the VIII European Symposium on Quantitative Structure-Activity Relationships, Sorrento, Italy.9-13 September 1990 - European Symposium on Quantitative Structure-Activity Relationships (1990 : Sorrento, Italy); Silipo, C. (Amsterdam : Elsevier, 1991)
42